General principles and potential organizational gains of Customer Relationship Management System implementation for Municipal Government structures in Armenia - Avetyan, Arman; Martirosyan, Goharik; Baghdasaryan, Svetlana (Acciones e Investigaciones Sociales, 2025)
This study explores the implementation and impact of a Customer Relationship Management (CRM) System within the municipal administration of Yerevan, focusing on the Citizen Complaint and Request Service. Employing a mixed-methods approach, the research includes a needs assessment, pilot implementation, and evaluation through qualitative and quantitative data collection. Key findings reveal significant improvements in service delivery times, personalized interactions, and operational efficiency post-implementation. Challenges identified include technical adjustments and initial employee resistance, addressed through continuous support and training. The study fills a significant gap in understanding CRM applicability in the public sector and offers a practical framework for achieving tangible improvements in municipal governance, supporting the broader goal of digital transformation in Armenia. The successful implementation of CRM systems in municipal services can serve as a model for other state governance structures, promoting a customer-oriented administrative culture.
Keywords: competence; transformation; client-oriented model; foreign experience; administrative structures